Evaluación de riesgos laborales y su incidencia en la salud de los trabajadores en la empresa pasec s.a." Pallasco Survey Engineering Construction, ubicado en la ciudad de Quito, barrio Salvador Celi, en el periodo 2015-2016 - Chanatasig Cajamarca, Jaime Gustavo (2016)
This research aims to evaluate occupational hazards, developed at PASEC SA "Pallasco Survey Engineering Construction company the Quito city, the research raises a field research, using tools such as the survey, with the results of the surveys, it was determined that workers are exposed to occupational hazards, researchers proceeded to the development of the Matrix occupational hazards GTC 45, identifying the Physical hazards (Noise) factors Hazard Mechanic (sharp tools management, Work different level), Biological hazards (poisonous or venomous animals), Risks Ergo (physical overexertion, repetitive motion, micro movements hand-fingers and forced position)….